Identification and Mapping of Critical Land Level in Probolinggo District Using Geographic Information System (GIS) Techniques (Case Study: Sumberasih, Wonokerto Sub-district, Bantaran, Maron, Krejengan, Tegal Siwalan and Pakuniran) - Siswanto; Purwadi (Future Science, 2020)
Based on research on land damage in 2019 in the highland area of ??Probolinggo, it was categorized as light to moderate damage. Follow-up research in the middle plains that have the potential to experience land damage due to intensive land use without paying attention to conservation principles, with an indication that the production and income of farmers continue to decline. The research aims to identify the status of critical land and compile a database of critical land for the medium lands of Probolinggo district including Sumberasih, Wonomerto, Bantaran, Maron, Krejengan, Tegalsiwalan, and Pakuniran. The research method for the distribution of critical land using the Geographic Information System is divided into the main activity stages, namely the compilation of databases and data analysis. Database preparation begins with data collection, supporting maps, and literature study. Meanwhile, data analysis used map overlay analysis. The analysis for the preparation of spatial data for critical land consists of 3 stages: overlapping, editing attribute data, and tabular analysis. The level of erosion in the 7 sub-districts of the study area includes very heavy (SB) in the open land of Pakuniran and residential land in Krejengan, the level of gravity on empty land, dryland in Pakuniran, and settlements in Pakuniran, Tegalsiwalan, and Maron. The research area includes 7 districts in Probolinggo which has an area of ??36,017.68 ha, with a non-critical status of 15,613.22 ha (43.35%). Critical potential 10,942.66 ha (30.38%), rather critical 8,134.56 ha (22.58%). critical 196.23 ha (0.54%) and very critical 1.131.01 ha (3.14%).